Effects of Hydrofluoroalkane and Dry Powder-Formulated Corticosteroids on Sputum Inflammatory Markers in Asthmatic Patients - Hans-Peter Hauber; Rame Taha; Celine Bergeron; Vladimir Migounov; Qutayba Hamid; Ron Olivenstein (Canadian Respiratory Journal)
BACKGROUND: Inhaled corticosteroids are powerful drugs that can suppress airway inflammation in asthmatic patients. Deposition of most of the inhaled corticosteroid occurs mainly in the central airways. However, a new hydrofluoroalkane formulation of beclomethasone dipropionate (HFA-BDP) is preferentially deposited in the distal airways. Inflammatory characteristics of induced sputum have been shown to differ in samples collected early after sputum induction compared with later.